Status and Environmental Impact of Emissions from Thermal Power Plants in India - Yadav S.; Prakash R. (My University, 2025)
The main emissions from coal combustion at thermal power plants are carbon dioxide (CO2), nitrogen oxides, sulfur oxides, chlorofluorocarbons (CFCs), and airborne inorganic particles such as fly ash and soot; CO2, methane, and CFCs are greenhouse gases. These emissions are considered to be partially responsible for harmful global climate change. This review summarizes the status of thermal power plants in India and their various types of emissions that directly or indirectly produce harmful effects on the environment and human health. Moreover, it focuses on various types of preventive measures used to avoid/minimize emissions. © 2014 Copyright © Taylor & Francis Group, LLC.